POLA KOMUNIKASI VISUAL BAHASA ARAB DI PONDOK PESANTREN MODERN DARUSSALAM GONTOR PONOROGO JAWA TIMUR - Kiki Nurjaman (Linimasa : Jurnal Ilmu Komunikasi, 2022)
ABSTRACT Islamic boarding schools are currently an alternative choice in continuing education. Since the entry of the pesantren system into Indonesia, Islamic boarding schools in Indonesia have continued to develop. Thus giving rise to the paradigm of santri graduates having their own values, which depend on the advantages or characteristics of the pesantren education. One of them is Pondok Modern Darussalam Gontor Ponorogo, East Java, which is famous for the excellence of its students by communicating in Arabic. The cottage, which is known as Gontor, was founded in 1926, and has a different system from other Islamic boarding schools. Arabic and English are tools for social interaction in everyday life. The students who have just entered Gontor are no exception. For this reason, from this research, it is possible to understand self-concept, the meaning of symbolic objects, the meaning of symbolic actions, and shared meaning among the residents of the cottage, which are conveyed through visual communication.